Benefits of sleep on reduction of injury and illness in Division I female soccer players - Franks, C.; Phillips, J.; Armstrong, K.; Andre, T.; Jo, J.; Valliant, M. (Scientific Journal of Sport and Performance, 2024)
Injuries in soccer athletes continues to rise and there is a cause for concern. Collegiate athletes have physically demanding workloads and struggle to sleep an adequate amount each night. A potential association is how sleep could play a role in an athletes` injury. 24 NCAA DI women`s soccer athletes were utilized during the Fall 2019 season. Athletes self-reported their daily hours slept and the athletic trainer tracked and classified athletes` injury and illness status: no-injury, medical attention injury, or time loss injury. K-mean clustering was utilized to classify the athletes into 3 groups: injury/illness-free group (n=12), mild-to-moderate injury/illness group (n=7), and heavy injury/illness group (n=5). Sleep was statistically significantly lower in the heavy-injury group than other groups and small effect sizes were detected (d31 = .282, p < .001; d32 = .278, p < .001). Based on the data, it appears hours slept plays a factor in female soccer athletes` risk of injury.